Black women in new South literature and culture - Johnson, Sherita L. (American popular history and culture (Routledge (Firm)), 2009)
This book focuses on the profound impact that racism had on the literary imagination of black Americans in the South. Johnson argues that it is impossible to consider what the "South" and what "southernness" mean without looking at how black women have contributed to and contested any unified definition of that region.